Rapid, Sensitive, and Sustainable Reversed-Phase HPTLC Method in Comparison to the Normal-Phase HPTLC for the Determination of Pterostilbene in Capsule Dosage Form - Prawez Alam (Processes, 2021)
The greenness evaluation of literature analytical methods for pterostilbene (PT) analysis was not performed. Accordingly, the rapid, sensitive, and green/sustainable reversed-phase high-performance thin-layer chromatography (RP-HPTLC) method was developed and compared to the normal-phase (NP)-HPTLC (NP-HPTLC) for the estimation of PT with a classical univariate calibration. The RP quantification of PT was performed using green solvent systems; however, the NP analysis of PT was performed using routine solvent systems. The PT was detected at 302 nm for both of the methods. The greenness scores for the current analytical assays were evaluated by the analytical GREEnness (AGREE) metric approach. The classical univariate calibration for RP and NP methods indicated the linearity range as 10–1600 and 30–400 ng band−1, respectively. The RP method was more reliable for PT analysis compared to the NP method. The PT contents in commercial capsule dosage form were found to be 100.84% using the RP method; however, the PT contents in commercial capsule dosage form were determined as 92.59% using the NP method. The AGREE scores for RP and NP methods were 0.78 and 0.46, respectively. The sustainable RP-HPTLC assay was able to detect PT in the presence of its degradation products, and hence it can be considered as a selective and stability-indicating method. Accordingly, the RP-HPTLC method with univariate calibration has been considered as a superior method over the NP-HPTLC method for PT analysis.